Beyond Resolution 2347 (2017): The Search for Protection of Cultural Heritage from Armed Non-State Groups - Giulia Baj (Constitutional Review, 2021)
One expression of cultural rights is the right to enjoy cultural heritage. However, the latter is not efficiently protected in situations of armed conflict. In many cases, armed non-State groups (ANSGs) have destroyed or looted cultural heritage items. The United Nations Security Council has intervened with Resolution 2347 (2017), welcomed by many as a milestone in the international protection of cultural heritage in conflict situations. However, this Resolution presents several limitations. The protection of cultural heritage from destruction and exploitation does not appear as the main focus, but rather as a means to fight terrorist groups. The attacks against cultural heritage are considered “war crimes”, but only “under certain circumstances”. The Resolution encourages States “that have not yet done so to consider ratifying” treaties on the issue in question; however, these instruments are treaties drafted and ratified by States. Problems of compliance by non-State actors, as ANSGs, arise. Hence, the capacity of theResolution to effectively protect cultural heritage in conflicts involving ANSGs is debated. This paper analyses the text of Resolution 2347 (2017), resorting to traditional means of interpretation to highlight its limitations, and considers how a general sense of the necessity to protect cultural heritage from attacks committed by ANSGs has emerged, as demonstrated by the International Criminal Court's Al Mahdi case. The paper then considers other ways to guarantee the protection of cultural heritage from ANSGs. A proposal for stronger protection of cultural heritage by States through both international humanitarian law (IHL) and international human rights law (IHRL) is presented. In particular, the connection between the protection of cultural heritage, the guarantee of cultural rights and other human rights is presented, resorting to instruments of doctrine and analyzing instruments of practice. Finally, the case for the stronger international cooperation for the protection of cultural heritage is made; problems of compliance by ANSGs may persist, but the systematic destruction of cultural heritage items can be considered a violation of cultural rights, thus requiring the cooperation of all international stakeholders.